3R Electronics: Scalable Fabrication of Resilient, Repairable, and Recyclable Soft-Matter Electronics - Tavakoli, Mahmoud (2022)
E-waste is rapidly turning into another man-made disaster. It is proposed that a paradigm shift toward a more sustainable future can be made through soft-matter electronics that are resilient, repairable if damaged, and recyclable (3R), provided that they achieve the same level of maturity as industrial electronics. This includes high-resolution patterning, multilayer implementation, microchip integration, and automated fabrication. Herein, a novel architecture of materials and methods for microchip-integrated condensed soft-matter 3R electronics is demonstrated. The 3R function is enabled by a biphasic liquid metal-based composite, a block copolymer with nonpermanent physical crosslinks, and an electrochemical technique for material recycling. In addition, an autonomous laser-patterning method for scalable circuit patterning with an exceptional resolution of <30 µm in seconds is developed. The phase-shifting property of the BCPs is utilized for vapor-assisted "soldering" circuit repairing and recycling. The process is performed entirely at room temperature, thereby opening the door for a wide range of heat-sensitive and biodegradable polymers for the next generation of green electronics. The implementation and recycling of sophisticated skin-mounted patches with embedded sensors, electrodes, antennas, and microchips that build a digital fingerprint of the human electrophysiological signals is demonstrated by collecting mechanical, electrical, optical, and thermal data from the epidermis.